THE EFFECTIVENESS OF PODCAST TO IMPROVE LISTENING SKILL IN NARRATIVE TEXT - Rinaepi; Putri Septiana Mubarokah; Henni Rosa Triwardani (Universitas Islam Al-Ihya Kuningan, 2021)
The purpose of the study is to find out the effectiveness of Podcast for improving listening skill and building comprehension for students on Narrative text. This research uses quasy experimental design. They were 18 tenth grade students of SMK Darul Ulum Kuningan as the research subject . they were devided into two groups ; Experimental and Control Group . Pre-test and post-test was used as the instruments in order to take data collection. Furthermore, the researcher analyzed and interpreted through quantitative procedure by SPSS 23.0 version. The result showed in the post-test of experiment group was higher than the mean score of the pre-test, which the mean of post-test was 84.00, and the pre-test was 58.75.Based on the statistical analysis using T-test, the result indicates that the significant value (sig-2 tailed) was 0,000 and it was lower than 0.05 0.000 < 0.05) and t-test value was 7.206 > t-table 2.145. It represented that there was a significant improvement of students` listening skill on Narrative text before and after being taught by using Podcast. the researcher takes the conclusion that Podcast is effective used in teaching learning listening at the tenth grade students of SMK Darul Ulum Kuningan.